Ensuring multisectoral action on the determinants of reproductive, maternal, newborn, child, and adolescent health in the post-2015 era. (14th September 2015) - Rasanathan, Kumanan; Damji, Nazneen; Atsbeha, Tesmerelna; Brune Drisse, Marie-Noel; Davis, Austen; Dora, Carlos; Karam, Azza; Kuruvilla, Shyama; Mahon, Jacqueline; Neira, Maria; Villar Montesinos, Eugenio; von Zinkernagel, Deborah; et al.
Abstract : Kumanan Rasanathan and colleagues explain how integrating action on determinants of women's, children's, and adolescents' health beyond the health sector into core health strategies is crucial to achieving sustainable development goal targets to end preventable deaths and ensure healthy lives